2012
DOI: 10.1002/er.2983
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of a composite laminate hydrogen storage vessel

Abstract: SUMMARY The purpose of this study is to optimize the design of a composite laminate hydrogen storage vessel for minimizing stress concentration. The optimum design of this study uses the finite‐element method combined with a simplified conjugated gradient method (SCGM) and genetic algorithm (GA) to find the minimization of von Mises stress of the composite laminate hydrogen storage vessel. In this study, a composite laminate hydrogen storage vessel with an aluminum liner and a carbon fiber/epoxy layer are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…As a result, recent constructions of hydrogen vehicles presented by the world's major manufacturers are based on the use of highly compressed gas (CGH2) as the most mature hydrogen storage technology. A significant progress in the design of lightweight composite cylinders made it allowable to increase the pressure of hydrogen stored on-board up to 350-700 bar and thus to reach gravimetric capacity of 5%-6.5% [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, recent constructions of hydrogen vehicles presented by the world's major manufacturers are based on the use of highly compressed gas (CGH2) as the most mature hydrogen storage technology. A significant progress in the design of lightweight composite cylinders made it allowable to increase the pressure of hydrogen stored on-board up to 350-700 bar and thus to reach gravimetric capacity of 5%-6.5% [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The von Mises equivalent stress was chosen to compare both the liner and the composite since in the absence of relevant shear stress in the composite, it is expected to yield results similar to other stress criteria. Likewise, Lin et al 14 designed composite pressure vessels for hydrogen storage based on the minimization of the von Mises stress in the metallic liner and composite layers. They reported that thickness plays a dominant role, but winding angle is not negligible.…”
Section: Stress Analysismentioning
confidence: 99%
“…The numerical design is developed by combining a direct finite element solver with an optimal method in the genetic algorithm (GA). A finite element analysis model, COMSOL, is used as the subroutine to solve the heat and mass transfer profile associated with the variation in the geometry of the heat sink during an iterative optimal process [17].…”
Section: Introductionmentioning
confidence: 99%